Agathokleous, Rafaela - (:unkn) unknown (My University, 2026)
Rafaela Agathokleous was born in Limassol, Cyprus on June, 1990. She studied Mechanical Engineering and Materials Science Engineering at Cyprus University of Technology until 2012. She then had her Master of Science (MSc) in the Department of Engineering and Design at Brunel University London in Sustainable Energy Technologies and Management where she graduated in 2013. Then she worked as a research associate in various research projects in Cyprus University of Technology while at the same time performed her PhD research which was completed in 2017. The research topic of her PhD was the thermal analysis of naturally ventilated building integrated photovoltaic systems. During her PhD studies, in 2015 she earned a scholarship foundation from the Cyprus State Scholarship Foundation and in 2016 a scholarship from the A.G. Leventis Foundation. She has 8 journal scientific publications, more than 15 conference publications and 3 book contributions on aspects concerning the characterisation of crystalline PV panels, optimisation of thermosiphon solar water heaters, building integrated PVs and solar thermal systems. Her special fields of interest include applications of Renewable Energy Sources (RES) and especially Solar Energy. Additionally, she is involved in editorial, holding the position of assistant editor at the Energy the International Journal of Elsevier, and she is a reviewer in Renewable Energy and Solar Energy journals as well. Rafaela is a member at the Chartered Institution of Building Services Engineers (CIBSE) and member at the Cyprus Scientific and Technical Chamber (ETEK). Rafaela is involved in teaching at Cyprus University of Technology the last years, mainly on the Heat and Mass Transfer module, and Programming with Fortran.